2016
DOI: 10.1177/1074248416663647
|View full text |Cite
|
Sign up to set email alerts
|

Combination Use of Clopidogrel and Proton Pump Inhibitors Increases Major Adverse Cardiovascular Events in Patients With Coronary Artery Disease

Abstract: The combination use of clopidogrel and certain types of PPIs (omeprazole, lansoprazole, esomeprazole, pantoprazole) increases the risk of MACE in patients with coronary artery disease. Only in the RMs of CYP2C19, PPIs were associated with significantly increased MACE in patients coadministered with clopidogrel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 41 publications
1
25
0
9
Order By: Relevance
“…[4][5][6][7] However, in the cardiovascular field, most analyses have focused on the association of PPI comedication with adverse cerebrocardiovascular events. [7][8][9][10] A recent study showed that clopidogrel could increase the risk of bleeding when ad-ministered to patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). 11) Because PPIs significantly reduce the risk of gastrointestinal (GI) bleeding associated with antiplatelet therapy, they are often administered in combination with clopidogrel.…”
mentioning
confidence: 99%
“…[4][5][6][7] However, in the cardiovascular field, most analyses have focused on the association of PPI comedication with adverse cerebrocardiovascular events. [7][8][9][10] A recent study showed that clopidogrel could increase the risk of bleeding when ad-ministered to patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). 11) Because PPIs significantly reduce the risk of gastrointestinal (GI) bleeding associated with antiplatelet therapy, they are often administered in combination with clopidogrel.…”
mentioning
confidence: 99%
“…Единственный ИПП, биодоступность которого не зависит от генетического полиморфизма CYP 2C19, -рабепразол, что обуславливает предсказуемость его кли-нического эффекта и хорошие результаты в эрадикации Helicobacter pylori [31], а также обеспечивает наимень-ший спектр лекарственных взаимодействий, что особен-но актуально у коморбидных пациентов при необходимо-сти приема других препаратов (клопидогрел, нестероид-ные противовоспалительные препараты, дигоксин, нифе-дипин, фенитоин, теофиллин и др.) [32][33][34][35][36][37][38].…”
Section: основными симптомами гэрб являются: изжога (жжение за грудинunclassified
“…Вероятность развития больших сосудистых событий оказалась одинаковой у пациентов, получавших ИПП четырех классов: омепразол, лансопразол, эзомепразол и пантопразол. Однако у больных, получавших рабепразол, повышения риска больших сосудистых событий не отмечено (отношение шансов = 1,03; 95% ДИ: 0,55-1,95) [11]. Наиболее вероятное объяснение этому -минимально выраженное взаимодействие рабепразола с системой цитохрома.…”
Section: заболевания пищевода и желудкаunclassified